Latency-Associated Viral Interleukin-10 (IL-10) Encoded by Human Cytomegalovirus Modulates Cellular IL-10 and CCL8 Secretion during Latent Infection through Changes in the Cellular MicroRNA hsa-miR-92a - Poole, Emma (J Virol, 2014)
The UL111A gene of human cytomegalovirus encodes a viral homologue of the cellular immunomodulatory cytokine interleukin 10 (cIL-10), which, due to alternative splicing, results in expression of two isoforms designated LAcmvIL-10 (expressed during both lytic and latent infection) and cmvIL-10 (identified only during lytic infection). We have analyzed the functions of LAcmvIL-10 during latent infection of primary myeloid progenitor cells and found that LAcmvIL-10 is responsible, at least in part, for the known increase in secretion of cellular IL-10 and CCL8 in the secretomes of latently infected cells. This latency-associated increase in CCL8 expression results from a concomitant LAcmvIL-10-mediated suppression of the expression of the cellular microRNA (miRNA) hsa-miR-92a, which targets CCL8 directly. Taking the data together, we show that the previously observed downregulation of hsa-miR-92a and upregulation of CCL8 during HCMV latent infection of myeloid cells are intimately linked via the latency-associated expression of LAcmvIL-10. IMPORTANCE HCMV latency causes significant morbidity and mortality in immunocompromised individuals, yet HCMV is carried silently (latently) in 50 to 90% of the population. Understanding how HCMV maintains infection for the lifetime of an infected individual is critical for the treatment of immunocompromised individuals suffering with disease as a result of HCMV. In this study, we analyze one of the proteins that are expressed during the “latent” phase of HCMV, LAcmvIL-10, and find that the expression of the gene modulates the microenvironment of the infected cell, leading to evasion of the immune system.